The Presentation of Complementary and Alternative Medicine Information in Canadian Midwifery Care - McKenzie, Pamela J.; Oliphant, Tami (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper uses discourse analysis to consider midwives’ and pregnant women’s discussions of conventional and complementary and alternative medicine interventions for inducing labour. Participants distinguished between “natural” and “medical” methods and used information sources based on both biomedical evidence and women’s experience to justify and challenge authority claims. Cet article utilise l’analyse du discours pour examiner les conversations des sages-femmes et des femmes enceintes au sujet des interventions en médecine traditionnelle, douce et alternative pour assister l’accouchement. Les participantes ont fait la distinction entre les méthodes « naturelles » et « médicales » et ont utilisé des sources d’information basées aussi bien sur les évidences biomédicales que sur l’expérience de femme pour justifier et remettre en question les autorités concernées.